2019
DOI: 10.1186/s12864-019-6164-5
|View full text |Cite
|
Sign up to set email alerts
|

Weighted single-step GWAS identified candidate genes associated with semen traits in a Duroc boar population

Abstract: BackgroundIn the pig production industry, artificial insemination (AI) plays an important role in enlarging the beneficial impact of elite boars. Understanding the genetic architecture and detecting genetic markers associated with semen traits can help in improving genetic selection for such traits and accelerate genetic progress. In this study, we utilized a weighted single-step genome-wide association study (wssGWAS) procedure to detect genetic regions and further candidate genes associated with semen traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 62 publications
0
23
0
1
Order By: Relevance
“…Investigating the genomic regions and molecular processes that control sperm quality has become a focus of interest in humans and in livestock including swine, in the latter case for its relevance on the sustainability of pig breeding and production [5,6,[10][11][12]. In fact, our results and those obtained by other groups [5][6][7][8], have shown that boar sperm quality has a genetic basis, which means that it can be selected for in breeding strategies.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Investigating the genomic regions and molecular processes that control sperm quality has become a focus of interest in humans and in livestock including swine, in the latter case for its relevance on the sustainability of pig breeding and production [5,6,[10][11][12]. In fact, our results and those obtained by other groups [5][6][7][8], have shown that boar sperm quality has a genetic basis, which means that it can be selected for in breeding strategies.…”
Section: Discussionmentioning
confidence: 54%
“…Marques et al [6] detected 16 and six QTL in Large White and Landrace pigs, respectively, associated with sperm motility, number of cells per ejaculate and morphological abnormalities. More recently, several QTL have been identified in a Duroc population associated to number of sperm cells, sperm motility, sperm progressive motility, total morphological abnormalities, coiled tail, bent tail, proximal droplets, distal droplets and distal midpiece reflex [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Genomic windows that explained higher than 1.0% of the total genetic variance were selected as candidate QTL regions associated with growth traits in this study, which was also used in previous studies [ 8 , 13 ]. Since the 0.8 Mb window explained on–average 0.0473% (100% divided by 2115 genomic regions) of the genetic variance, the 1% threshold is over 20 times the expected average genetic variance explained by the 0.8 Mb window.…”
Section: Methodsmentioning
confidence: 99%
“…In that case, the wssGWAS can be adopted, which weighs SNPs according to their effects that were calculated genomic estimated breeding values (GEBVs) via ssGBLUP. The wssGWAS method has been successfully applied to detect supplementary QTLs and candidate genes in domestic and aquaculture animals, such as carcass traits in Nellore cattle [ 11 ], growth and carcass traits in rainbow trout [ 12 ], and reproductive traits in pigs [ 13 ]. However, to our knowledge, few wssGWASs have been performed to study growth traits in purebred Duroc pigs.…”
Section: Introductionmentioning
confidence: 99%
“…GWAS have a greater capability than QTL mapping to detect causal SNPs in a smaller genetic range 12 . In recent years, many genes and molecular markers, regulate important traits, were identi ed using GWAS in livestock animals like pigs, cattle, sheep, and chickens 13,14 . Despite its unique potential and increased contribution to food security, comparatively less attention has been paid to camels compared to other livestock species 3 .…”
Section: Introductionmentioning
confidence: 99%